A framework for comparing large-scale survey assessments: contrasting India’s NAS, United States’ NAEP, and OECD’s PISA - van Rijn, Peter; Por, Han-Hui; McCaffrey, Daniel F.; Bhaduri, Indrani; Bertling, Jonas (Frontiers in Education, 2024)
Large-scale survey assessments (LSAs) are important tools for measuring educational outcomes and shaping policy decisions. We present a framework for comparing LSAs to facilitate studying the impact of design choice on the precision of results, contrasting India’s National Achievement Survey (NAS), the United States’ National Assessment of Educational Progress (NAEP), and the OECD’s Programme for International Student Assessment (PISA). Our framework focuses on four key elements: sampling design, assessment design, analysis methodology, and reporting. The notion of total survey error, which is the accumulation of errors across the four key elements, can be used for both designing and evaluating LSAs. As example, we compare statistics that are commonly (but not always) reported from NAS, NAEP, and PISA to summarize outcomes related to sampling, measurement, and reporting. Our examination reveals several key similarities and differences among the three assessments, thereby highlighting the nuanced ways in which each LSA is tailored to meet the specific needs of their purpose and the challenges they face.